Antenatal Toxoplasma gondii, Rubella and Cytomegalovirus Infection Screening Among Pregnant Women Attending Tertiary University Hospital - Beril Gurlek; Sabri Colak (Medical Network, 2019)
Objective: The present study was designed to determine the seroprevalance of Toxoplasma gondii, Rubella, and cytomegalovirus, to investigate the frequency of low and high avidity results among pregnant women and to contribute to the data of our country with the results obtained. Study Design: In the present study, the hospital records of the women who applied to the antenatal outpatient of the Rize Recep Tayyip Erdoğan University Medical Faculty during the first trimester between January 2016 and October 2018 were retrospectively reviewed. Toxoplasma gondii, RRubella and cytomegalovirus IgM, IgG and IgG avidity results were evaluated. Result: IgM positivity was found to be 0.83% (29/3490) for Toxoplasma gondii, 0.92% (32/3459) for Rubella and 1.90% (65/3404) for cytomegalovirus; IgG positivity was found to be 33.64% (1174/3490) for Toxoplasma gondii, 90.70% for Rubella (3140/3459), and 99.17% (3376/3404) for cytomegalovirus. Avidity of Toxoplasma gondii was found to be low (3.70%) in 1 patient, borderline (11.11%) in 3 patients, and high avidity in 23 patients (85.18%). Avidity of cytomegalovirus was found to be low (1.75%) in 1 patient, borderline (3.50%) in 2 patients and high avidity (94.73%) in 54 patients. Avidity of Rubella was found to be low (4%) in 1 patient, and high avidity (96%) was found in 24 patients. Conclusions: In our study, although the prevalence of acute infection with Rubella, cytomegalovirus and Toxoplasma gondii was shown to be low in pregnancy in Rize province, serological screening tests for monitoring and informing high-risk groups that are particularly seronegative appear to be important.